Gender Representation of Code Switching in Students' Presentation: How Do They Differ? - Kenzo Akbar, Muhamad; Hd. Fadhilah, Izzah; Safnil, Safnil (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Comprehending the impact of gender on code-switching behaviors in student presentations is essential for educators to create effective communication tactics and inclusive teaching techniques. The objective of this study is to examine the occurrence and patterns of code-switching in student presentations, with a particular emphasis on gender disparities. The study aims to investigate the differences between male and female students in their utilization of intra-sentential, inter-sentential, and tag-switching techniques during presentations. This study utilized a qualitative methodology. The researchers examined 12 presentations and identified occurrences of code-switching according to Poplack's (1980) theory. The results indicated notable disparities between genders in code-switching tendencies. Female students exhibited a greater occurrence of intra-sentential switching, with a frequency of 73%, in contrast to male students, who had a frequency of 27%. Inter-sentential switching is the most frequently utilized sort of code-switching, while Tag-switching is the least commonly employed by students. The study's findings indicate that female students have a higher tendency to code-switch during presentations, namely in the forms of intra-sentential and inter-sentential code-switching. These observations emphasize the importance for educators to take into account gender dynamics when creating teaching practices that employ code-switching as a means of efficient communication.